2017
DOI: 10.1016/j.ymeth.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of threonyl-tRNA synthetase on angiogenesis-related responses

Abstract: Several recent reports have found a connection between specific aminoacyl-tRNA synthetases and the regulation of angiogenesis. As this new area of research is explored, it is important to have reliable assays to assess the specific angiogenesis functions of these enzymes. This review provides information about specific in vitro and in vivo methods that were used to assess the angiogenic functions of threonyl-tRNA synthetase including endothelial cell migration and tube assays as well as chorioallantoic membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Further studies are warranted to determine the connection between human colon cancer and plasma metabolomic profiles of the citrate cycle pathway in the context of obesity. Second, arginine biosynthesis and aminoacy l- tRNA biosynthesis are two pathways, which are involved in endothelial cell migration and angiogenesis in tumorigenesis [ 38 , 39 ]. However, there are scant data examining plasma metabolomic profiling in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are warranted to determine the connection between human colon cancer and plasma metabolomic profiles of the citrate cycle pathway in the context of obesity. Second, arginine biosynthesis and aminoacy l- tRNA biosynthesis are two pathways, which are involved in endothelial cell migration and angiogenesis in tumorigenesis [ 38 , 39 ]. However, there are scant data examining plasma metabolomic profiling in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…TARS is an angiogenesis‐regulating factor as it stimulates the migration of vascular endothelial cells and promotes the formation of blood vessel. 35 Previous studies reported that TARS overexpression was positively correlated with the stage of ovarian cancer 36 and pancreatic cancer cell migration. 37 Our data confirmed elevated TARS expression in GC tissues and paralleled to expression level of VEGFR, an important angiogenic signaling molecule.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, polymyositis/dermatomyositis (PM/DM), which is also related to the ThrRS mutation, is usually complicated by interstitial lung disease that seriously impacts the patient's life 32 . Furthermore, ThrRS also engages in angiogenesis 33 . The zebrafish mutant presents disorganized vessels with abnormal branching of the intersegmental vessels and an aberrant brain vascular network 34 .…”
Section: Introductionmentioning
confidence: 99%
“…32 Furthermore, ThrRS also engages in angiogenesis. 33 The zebrafish mutant presents disorganized vessels with abnormal branching of the intersegmental vessels and an aberrant brain vascular network. 34 Its overexpression is correlated with progression of human ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%